Radiological assessment of alveolar bone loss associated with overhanging restorations: A retrospective cone beam computed tomography study - TARÇIN, BİLGE; GÜMRÜ TARÇIN, BİRSAY; İDMAN, ENDER (My University, 2022)
Background/purpose: Studies suggested that presence and size of overhanging restoration margins play role in alveolar bone loss. The aim of this study was to determine the prevalence and distribution of overhanging approximal restorations, to evaluate the effect of presence and size of overhang on bone loss using cone beam computed tomography (CBCT) reformatted panoramic images, and to encourage the use of CBCT in retrospective studies on restorative dentistry. Materials and methods: CBCT images of 382 patients with approximal restorations were included in the study. On CBCT images, alveolar bone loss adjacent to each restored surface was determined and compared to the control tooth. The overhang size was measured and categorized as small, medium, or large. Data obtained were evaluated statistically using Kruskal Wallis, Mann Whitney U, chi-square, and one-sample chi-square tests with a significance level set at P < 0.05. Results: A total of 216 (32.4%) surfaces with overhanging restorations were detected in CBCT images. The number of overhanging surfaces with alveolar bone loss (71.3%) was higher than the control surfaces with bone loss (49.1%) (P < 0.05). The amount of bone loss adjacent to overhanging surfaces (2.28 1.69 mm) was significantly higher compared to control surfaces (1.53 1.73 mm) (P < 0.05). However, the same trend applied to the surfaces without overhang and their controls. The amount of bone loss was not correlated with the overhang size (P > 0.05).
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Alveolar bone loss; Cone beam computed tomography; Dental restoration; Overhanging; Alveolar bone loss; Cone beam computed tomography; Dental restoration; Overhanging